Dose‐dependent cytotoxicity induced by pristine graphene oxide nanosheets for potential bone tissue regeneration. Issue 3 (4th December 2019) - Zhang, Xiliu; Wei, Changbo; Li, Yiming; Li, Ye; Chen, Guanhui; He, Yi; Yi, Chen; Wang, Chao; Yu, Dongsheng
Abstract: This study was aimed to investigate the toxic effects of pristine graphene oxide (GO) nanosheets on bone‐marrow‐derived mesenchymal stem cells (BMSCs), a type of traditional seed cells in tissue regeneration engineering. First, a GO suspension was prepared and characterized by transmission electron microscopy, Fourier transform infrared spectroscopy, and Raman shifts. Then, rat BMSCs were isolated and characterized. Subsequently, cell proliferation, membrane integrity, cell cycle, cell apoptosis, mitochondrial membrane potential (MMP), and reactive oxygen species (ROS) were measured. In addition, relevant proteins of the mitochondrial apoptotic pathway and autophagy were analyzed. Our results showed that a high concentration of GO inhibited cell viability and membrane integrity, while cell apoptosis and cell‐cycle arrest were induced by GO. Further, GO significantly increased ROS generation and MMP loss with an upregulation of Cleaved Caspase‐3, LC3‐II/I, and Beclin‐1 and a downregulation of Bcl‐2 and Caspase3. We concluded that the toxic effects of GO on BMSCs occurred in a dose‐dependent manner via the mitochondrial apoptotic pathway and autophagy.